A guidebook on the compliance review function of ADB accountability mechanism for affected people, nongovernment organizations, and civil society organizations.
ADB Accountability Mechanism is the grievance redress platform of last resort for people and communities who may be unduly, adversely, or potentially affected by ADB assisted projects. This guidebook is one in a series of four guidebooks that aims to aid comprehension of the compliance review and its processes, particularly the role of each of the stakeholders in the proceedings. The series is intended for (i) ADB Management and staff, (ii) governments, (iii) affected people and their representative or partner nongovernment organizations or civil society organizations, and (iv) private sector borrowers.